2022
DOI: 10.1038/s41398-022-02017-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential grey matter structure in women with premenstrual dysphoric disorder: evidence from brain morphometry and data-driven classification

Abstract: Premenstrual dysphoric disorder (PMDD) is a female-specific condition classified in the Diagnostic and Statical Manual—5th edition under depressive disorders. Alterations in grey matter volume, cortical thickness and folding metrics have been associated with a number of mood disorders, though little is known regarding brain morphological alterations in PMDD. Here, women with PMDD and healthy controls underwent magnetic resonance imaging (MRI) during the luteal phase of the menstrual cycle. Differences in grey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…As for brain surface measures, one study investigating the cortical thickness in women with PMDD and controls, yielded negative results ( Syan et al, 2018 ), while recent findings indicate several bidirectional relationships between both mental and physical PMDD symptoms and four different surface architecture indices (cortical thickness, gyrification index, sulcal depth, cortical complexity) for frontal and parahippocampal regions ( Dubol et al, 2022b ). Furthermore, we demonstrated that grey matter volume is a potential neuroanatomical signature of PMDD, as indicated by data-driven classification of women with PMDD compared with healthy controls based on structural MRI ( Dubol et al, 2022a ). However, to the best of our knowledge, the neural signatures of treatment effects on PMDD or correlates related to PMDD symptoms relief have yet to be investigated.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…As for brain surface measures, one study investigating the cortical thickness in women with PMDD and controls, yielded negative results ( Syan et al, 2018 ), while recent findings indicate several bidirectional relationships between both mental and physical PMDD symptoms and four different surface architecture indices (cortical thickness, gyrification index, sulcal depth, cortical complexity) for frontal and parahippocampal regions ( Dubol et al, 2022b ). Furthermore, we demonstrated that grey matter volume is a potential neuroanatomical signature of PMDD, as indicated by data-driven classification of women with PMDD compared with healthy controls based on structural MRI ( Dubol et al, 2022a ). However, to the best of our knowledge, the neural signatures of treatment effects on PMDD or correlates related to PMDD symptoms relief have yet to be investigated.…”
Section: Introductionmentioning
confidence: 60%
“…Given the novelty and the exploratory nature of the study, the present findings cannot be conclusive on the absence of an SPRM effect on brain architecture. Sparse and inconsistent findings on the anatomical signatures of PMDD are documented and the methodological differences are noteworthy ( Dubol et al, 2020 ); however, recent findings do seem to confirm differential grey matter structure in PMDD ( Dubol et al, 2022a ). These women suffer from this disorder for decades throughout their reproductive years ( Rapkin and Winer, 2009 ) and since luteal-phase structural signatures of the disorder are still to be established, it is likely that three months might not be enough to observe effects on grey matter.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, these differences extend to the prenatal period [41]. Hence, developmental origins of differences between women with PMDD and healthy controls present [42], just as there are significant sex differences that are attributed in part to brain morphology.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are interesting for several reasons. Firstly, these brain regions have been shown to vary functionally across the menstrual cycle in subjects with PMDD [58], and have thus previously been implicated in the pathophysiology of PMDD. Secondly, the regions are implicated in emotion processing, whereby the amygdala is a key node of emotion processing networks [35], and the PHG is involved in the early appraisal and encoding of the emotional significance of stimuli during the automatic regulation of emotion [59].…”
Section: Discussionmentioning
confidence: 99%